The Effect of Workload and Burnout on Employee Turnover Intention at PT. Mandiri Taspen KCP Palopo - Maharani, Putri; Saharuddin, Saharuddin; Rismawati, Rismawati; Harmanpreet, Harmanpreet (PT. EQUATOR SINAR AKADEMIA, 2025)
This study aims to analyze the simultaneous effects of workload and burnout on employee turnover intention at PT. Mandiri Taspen KCP Palopo. This study uses a quantitative approach with data collection techniques through the distribution of questionnaires to 36 respondents using a saturated sampling method. The method used is saturated sampling. The data used in this study are primary data collected directly from respondents through the distribution of questionnaires. Data analysis was conducted using the SPSS version 23 application. The results of the study indicate that Workload and Burnout simultaneously do not have a significant effect on employee turnover intention.